Analysis and management of avariation to a fluvial transport vessel caused by collision - Babis C; Chivu Oana; Dimitrescu A; Dascalu L; Niculae E; Iacobescu G; Semenescu A; Negoita O; Purcarea A (Journal of Research and Innovation for Sustainable Society, 2019)
In general, the body of the ship is a welded metal structure made up of the shell and bone. The paper aims is to analyze and present the solution for the collision damage to a river transport vessel. The problem is treated as in the case of a typical failure of welded constructions. In this regard, the fault will be described, after which the stages of the fault remedy will be presented.